Chapter 17 Authenticity beyond Authority? The Case of Handwritten Entertainment Fiction from the Chinese Cultural Revolution - Henningsen, Lena (Taylor & Francis, 2023)
Handwritten entertainment fiction (shouchaoben wenxue) circulated widely, albeit clandestinely, during the Cultural Revolution (1966-76), often in hasty handwriting on fragile paper. As a result, we are confronted with divergent witnesses without an identifiable original urtext. Divergence often extends to variant narratives of the "same" story, which in most cases lack a distinct author. Consequently, the authenticity of the narrative cannot be seen as an extension of an individual's authority. Rather, authenticity rests on a distinct narrative core which is embellished by variations in plot, style, or characterization of the protagonists. However, these texts are authentic historical sources providing insights into the realities and zeitgeist of the era: their materiality, including marginalia, illuminating the process in which these texts were created, circulated, and read. Often, their contents reflect on historical realities. We therefore discuss multiple copies of Three Journeys to Jiangnan, as well as introducing our own digital edition of the texts. They are rendered authentic by the contexts of their production and circulation, their material fragility, and the resulting instability in contents, that still retains a relational narrative core.